2021
DOI: 10.1029/2020jd033935
|View full text |Cite
|
Sign up to set email alerts
|

Blowing Snow at McMurdo Station, Antarctica During the AWARE Field Campaign: Surface and Ceilometer Observations

Abstract: Blowing snow (BLSN) is an impactful process in cold climates, affecting regional thermodynamics, radiation properties, and the surface mass balance of snow. Though it has significant climatic impacts, the process is still poorly understood and not widely included in weather and climate models. In 2016, the AWARE Field Campaign saw the deployment of a large suite of in situ and remote sensing instruments to McMurdo Station, Antarctica allowing for investigation of BLSN. A ceilometer‐based BLSN detection algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…To demonstrate the MI BLSN depth algorithm, two case studies are presented that represent the variety of BLSN events McMurdo station experiences. The selected case days are the same as those presented in Loeb and Kennedy (2021), which readers are referred to for more in-depth descriptions of meteorological background and BLSN detection. An additional case study for 10 February 2016 is shown in Supporting Information S1 (Figure S6).…”
Section: Example Case Studiesmentioning
confidence: 99%
“…To demonstrate the MI BLSN depth algorithm, two case studies are presented that represent the variety of BLSN events McMurdo station experiences. The selected case days are the same as those presented in Loeb and Kennedy (2021), which readers are referred to for more in-depth descriptions of meteorological background and BLSN detection. An additional case study for 10 February 2016 is shown in Supporting Information S1 (Figure S6).…”
Section: Example Case Studiesmentioning
confidence: 99%
“…The site deployed various instruments, such as a Vaisala CL31 ceilometer, surface meteorology systems and particle size and velocity disdrometer (Parsivel 2 ; manufactured by Ott Hydromet GmbH at Kempten, Germany). In addition, the Antarctic Meteorological Research Center (AMRC) at the University of Wisconsin-Madison has provided the three-hour periods observation results by human observers at McMurdo Station since 1999 [10].…”
Section: Instruments and Datamentioning
confidence: 99%
“…When there are no particles, the voltage signal of the photodiode is usually large. If the particles pass through the field of view, the output of the photodiode will be reduced to measure the shadow of the particles [10]. Parsivel 2 can directly measure the particle size and particle number and obtain the derived parameters, such as radar reflectivity and particle number density.…”
Section: Surface Meteorology Systemsmentioning
confidence: 99%
See 2 more Smart Citations